ANALYSIS OF WAGES AND BONUSES OF NON-ASN EMPLOYEES AT THE ACEH PROVINCIAL SOCIAL SERVICE : (Study According to the Concept of Ijârah 'ala Al-'Amâl) - Yuslukhalbi, Gunawan; Muhammad Yusran Hadi (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This article analyzes the wage and bonus system for non-civil servant employees (non-ASN) at the Aceh Provincial Social Service from the perspective of the Islamic economic contract Ijârah 'Ala al-'Amâl. The main issue addressed is the injustice between the significant contributions of non-ASN employees—who play a crucial role in public services—and the compensation they receive. Most wages remain below the Provincial Minimum Wage (UMP) and are not accompanied by allowances, bonuses, or social security, thereby creating a gap with civil servants (ASN) and raising concerns about legal certainty in employment relations. This study employs a normative-empirical approach with a descriptive qualitative method, using structured interviews and an examination of regulations as well as Islamic jurisprudence literature on muamalah. The findings reveal that employment agreements for non-ASN staff at the Aceh Provincial Social Service fulfill the essential pillars of the Ijârah contract, such as the contracting parties (aqid), namely the Social Service (as musta'jir) and the non-ASN employees (as ajîr), the object of the contract (ma'qud 'alaih), the agreed remuneration (ujrah), and the contractual declaration (sighat) of offer and acceptance. However, when assessed against the conditions of Ijârah, deficiencies are found, particularly due to workloads that do not align with the written contract, leading to invalidity in the object of the contract.